A (de)formed perception of the pathway to be taken during the PhD. The influence of time in the students’ eyes perception in becoming a researcher. - Coutinho, Isabel Ribau (Advances in Social Sciences Research Journal, 2020)
The PhD journey is different from all other activities in higher education. It ́s a period of construction of the research and is also a time for integration in the academy, in the field of research, and at the higher education system. During the enrolment in the PhD, the person’s growth and the live experience change the perception that the doctorate has of the PhD and the research journey. The experiences as a doctoral student and as a researcher under construction, who is supervised/oriented/ guided by a supervisor, shape the way of thinking and action regarding the institution and the academy but also influence the way they see and felt the PhD journey and their beliefs. It is argued in this paper that an initial (de)formed perception of the real PhD journey and supervision, may influence the satisfaction of the students with it, and the disappointment impact the option to leave the academy or to continue. The current paper describes the change in the perception, motives, and of the curriculum quality and adequacy to doctoral personal journeys, during the doctorate. But it also reflects a PhD students’ personal journey and their perceptions concerning the PhD supervisors, host institutions, and the academy.